"Réseau de Bragg sur fibre optique : application à la compensation de la dispersion chromatique dans les systèmes de transmission optique haut débit" - أكرم, دقاشي; كمال, ونيس; عبد الصمد, قحمص (University Of El Oued, 2020)
"Optical fiber is one of the most important communications media in communication system. Due to its versatile advantages and negligible transmission loss it is used in high speed data transmission. There are various types of optical fiber, the Fiber Bragg Grating (FBG) is commonly chosen as important components to compensate the dispersion in optical communication system. Because the low cost of filter for wavelength selection and low insertion loss, it has also customized reflection spectrum and wide bandwidth. The simulation of transmission system will be analyzed based on different parameters using OptiSystem simulator, This integrated simulation program is specially designed to simulate an optical communication system as it performs numerous system tests and optimizes the design of any virtual optical spot in the physical layer of a wide spectrum of meshes. The primary objective of this end-of-cycle project is the study and simulation of Bragg gratings and their applications to high-speed optical transmission systems" "إن الألياف البصرية هي واحدة من أهم وسائل الاتصال المستخدمة في أنظمة الاتصالات وقد تم استخدامها لنقل البيانات بسرعة عالية لمزاياها العديدة و الضياعات المهملة في عملية النقل، و يعتبر التشتت العامل الرئيسي الذي يحد من كفاءة الأداء.هناك أنواع مختلفة من معوضات التشتت في الألياف البصرية و لكن يعتبر ليف شبكة براغ هو الأكثر استخداما في تعويض التشتت في أنظمة الاتصالات البصرية، بسبب الكلفة المنخفضة للمرشح المستخدم لاختيار طول الموجة و انخفاض فقد الحقن، حيث يملك طيف انعكاس منفصل و عرض حزمة واسع . سوف يتم تحليل محاكاة لنظام الاتصالات استنادًا إلى معايير مختلفة باستخدام برنامج simulator Optisystem إن برنامج المحاكاة هذا متكامل ومصمم خصيصا لمحاكاة نظام الاتصال البصري حيث يقوم باختبارات عديدة للنظام. الهدف الأساسي لمشروع نهاية الدورة هذا هو دراسة ومحاكاة حواجز براغ وتطبيقاتها على أنظمة الإرسال الضوئية عالية السرعة."
Systeme de telecommunication مذكرة ماستر تخصص
Keywords: Optical fiber, chromatic dispersion, Bragg gratings.; الألياف البصرية , التشتت اللوني , شبكات براغ.